2019
DOI: 10.1155/2019/8509820
|View full text |Cite
|
Sign up to set email alerts
|

Multislice Computed Tomography Assessment of Airway Patency Changes Associated with Mandibular Advancement Appliance Therapy in Supine Patients with Obstructive Sleep Apnea

Abstract: The purpose of the present study was to measure the regional effects of the mandibular advancement appliance (MAA) on the upper airway of supine subjects with obstructive sleep apnea (OSA) using multislice computed tomography (MSCT). The subjects included 8 males and 5 females who were diagnosed with mild to moderate OSA and were referred to the Orthodontic Clinic of Hiroshima University Hospital, where they underwent MAA therapy. Using a CT scanner, baseline MSCT images were obtained from the subjects without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Certain studies with a similar design have observed augmentations of the upper airway volume once the MAD was placed. In the study of Matsumara et al, 46 regarding our results, the increase of the airway volume (15.5 cm 3 –19.1 cm 3 ) after the placement of a MAD was much bigger. Probably, the fact that the CBCT in the study of Matsumara et al 46 was taken in a supine position explains the greater increase in this sample.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Certain studies with a similar design have observed augmentations of the upper airway volume once the MAD was placed. In the study of Matsumara et al, 46 regarding our results, the increase of the airway volume (15.5 cm 3 –19.1 cm 3 ) after the placement of a MAD was much bigger. Probably, the fact that the CBCT in the study of Matsumara et al 46 was taken in a supine position explains the greater increase in this sample.…”
Section: Discussionsupporting
confidence: 56%
“…In the study of Matsumara et al, 46 regarding our results, the increase of the airway volume (15.5 cm 3 –19.1 cm 3 ) after the placement of a MAD was much bigger. Probably, the fact that the CBCT in the study of Matsumara et al 46 was taken in a supine position explains the greater increase in this sample. Interestingly, this author analysed as well, the tridimensional changes of the soft tissues once the MAD was placed.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation